2006
DOI: 10.1021/jp0624698
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of M(OH)1,2,3 (M = Mn, Fe, Co, Ni) Molecules in Solid Argon and the Character of First Row Transition Metal Hydroxide Bonding

Abstract: Reactions of laser-ablated Mn, Fe, Co, and Ni atoms with H(2)O(2) and with H(2) + O(2) mixtures in excess argon give new absorptions in the O-H and M-O stretching regions, which are assigned to metal dihydroxide and trihydroxide molecules, M(OH)(2) and M(OH)(3). Isotopic substitutions (D(2)O(2), (18)O(2), (16,18)O(2), D(2)) confirmed the assignments and DFT calculations reproduced the experimental results. The O-H stretching frequencies decreased in the dihydroxides from Sc to Zn. Mulliken and natural charge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…The peaks around n1 (451 cm À1 ) and n2 (584 cm À1 ) are originating from the stretching vibrations of the metal-oxygen bond characteristic of the spinel metal oxide [16]. The absorption peaks at n3 (1450 cm À1 ), n4 (1605 cm À1 ) and n5 (3437 cm À1 ) are assigned to the bending vibration of NH 4 , bending vibration of molecular water and OH-stretching vibration, respectively [17,18]. The FT-IR analysis revealed the formation of spinel Co 3 O 4 with the inclusion of oxyhydroxide phase.…”
Section: Ft-ir Studiesmentioning
confidence: 99%
“…The peaks around n1 (451 cm À1 ) and n2 (584 cm À1 ) are originating from the stretching vibrations of the metal-oxygen bond characteristic of the spinel metal oxide [16]. The absorption peaks at n3 (1450 cm À1 ), n4 (1605 cm À1 ) and n5 (3437 cm À1 ) are assigned to the bending vibration of NH 4 , bending vibration of molecular water and OH-stretching vibration, respectively [17,18]. The FT-IR analysis revealed the formation of spinel Co 3 O 4 with the inclusion of oxyhydroxide phase.…”
Section: Ft-ir Studiesmentioning
confidence: 99%
“…This means that Fe(OH)3 molecules affected the interfacial water structure or OH stretch mode of Fe(OH)3 itself as seen in the spectra. Previous IR absorption measurement of metal hydroxide in solid argon showed that the OH stretch mode of Fe(OH)3 is ~ 3670 cm -1 , similar to the value of free (non-hydrogen bonded) OH of a water molecule [25]. Since Fe(OH)3 will make a hydrogen bonding network with surrounding water molecules, OH vibrational frequency is expected to be redshifted appreciably.…”
Section: Resultsmentioning
confidence: 83%
“…This suggests ion-exchange mechanism of fluoride adsorption. Appearance of a new adsorption peak at 459 cm À1 might be corresponding to the Fe-F [33].…”
Section: Ftir Studiesmentioning
confidence: 99%